Hyperkalaemia in the emergency department: Epidemiology, management and monitoring of treatment outcomes. (11th April 2022) - Pollack, Kimberley; Manning, Kiri R; Balassone, Jacqueline; Bui, Calista; Taylor, David McD; Taylor, Simone E
Abstract: Objective: To describe the epidemiology, treatment and monitoring of treatment outcomes of patients presenting to the ED with hyperkalaemia. Methods: We undertook a retrospective observational study in a mixed adult/paediatric ED over five 3‐month periods. Consecutive patients were included if they had an initial serum or blood gas potassium ≥6.0 mmol/L. Patients were excluded if their principal diagnosis was diabetic ketoacidosis, their blood sample was haemolysed or the blood gas result was inconsistent with a subsequent serum potassium. Data were extracted from electronic medical records and two senior emergency registrars independently assessed available ECGs. Moderate and severe hyperkalaemia were potassium 6.0–6.4 and ≥6.5 mmol/L, respectively. Results: Overall, 392 patients were included (mean age 73.7 years, triage category 1 or 2 28.3%, admitted 91.3%). Three hundred and twenty‐one (81.9%, 95% confidence interval [CI] 77.6–85.5%) patients took one or more medications that predispose to hyperkalaemia and 335 (85.5%, 95% CI 81.5–88.7%) had one or more predisposing comorbidities. Two hundred and seventy‐one (69.1%, 95% CI 64.3–73.6%) patients had moderately severe and 121 (30.9%, 95% CI 26.4–35.7%) had severe hyperkalaemia. Two hundred and fifty‐nine (66.1%, 95% CI 61.1–70.7%) patients were administered at least one medication in ED to lower the potassium concentration and 51 (13.0%, 95% CI 9.9–16.8%) were dialysed. One hundred and eighty‐seven patients received intravenous insulin: 40 (21.4%) had documented biochemical hypoglycaemia, but 45 (24.1%) had no post‐insulin blood glucose level documented. Hyperkalaemia‐associated ECG changes were uncommon. Conclusion: Most ED patients with hyperkalaemia have identifiable clinical and medication‐related risk factors. Variations in care were widespread and monitoring for iatrogenic adverse events was suboptimal. Abstract : One in 250 ED patients had moderate or severe hyperkalaemia and most of these patients had identifiable clinical and medication‐related risk factors. Deficiencies in elements of management were identified; blood glucose levels were not consistently measured and iatrogenic biochemical hypoglycaemia occurred in a substantial proportion of patients administered insulin, and ECGs were not always recorded.